Successful outcome of a triplet pregnancy following laparoscopic myomectomy for infertility: a unique case report - Hymavathi, Kaliki; Tadisetti, Surekha; Devi Gottipati, Malini; T. C., Bhavana (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Infertility is a burning problem affecting 10-15% of the couples globally. The female factors contribute to about 40- 45% among which uterine factor is up to 10%. Presence of uterine myomas also significantly contribute to infertility. A conservative surgical approach like myomectomy is indicated for women in reproductive age both for psychological reasons as well as to preserve their reproductive potential. In recent years laparoscopic myomectomy (LM) has become the procedure of choice. Pregnancy outcome after myomectomy is a more significant concern especially with regard to the obstetric calamity of sudden uterine rupture due to the presence of an operative scar. The intensity of such complication will be considerably high when a triplet pregnancy occurs with a LM scar in the upper uterine segment with history of uterine cavity being opened during the myomectomy surgery. Managing such a case will be a difficult task to the attending clinician posing many unexpected clinical dilemmas. We are reporting a unique case of triplet pregnancy occurred following a LM resulting in successful maternal and fetal outcome. During the course of this pregnancy apart from considerable maternal distress due to uterine over distension many clinical problems like cervical insufficiency, pre eclampsia, polyhydraminos, intrauterine growth restriction (IUGR) and last but not the least severe postpartum haemorrhage (PPH) have been encountered and could be managed efficiently. An elective Caesarean section was performed at 33+4 weeks gestation delivering live triplets. Mother and all the three babies discharged from the hospital in good condition.